Carbon Stable Isotope Values in Plankton and Mussels Reflect Changes in Carbonate Chemistry Associated with Nutrient Enhanced Net Production - Oczkowski, Autumn; Taplin, Bryan; Pruell, Richard; Pimenta, Adam; Johnson, Roxanne; Grear, Jason (Frontiers in Marine Science, 2018)
Coastal ecosystems are inherently complex and potentially adaptive as they respond to changes in nutrient loads and climate. We documented the role that carbon stable isotope (δ13C) measurements could play in understanding that adaptation with a series of three Ecostat (i.e., continuous culture) experiments. We quantified linkages among δ13C, nutrients, carbonate chemistry, primary, and secondary production in temperate estuarine waters. Experimental culture vessels (9.1 L) containing 33% whole and 67% filtered (0.2 µm) seawater were amended with dissolved inorganic nitrogen (N) and phosphorous (P) in low (3 vessels; 5 µM N, 0.3 µM P), moderate (3 vessels; 25 µM N, 1.6 µM P), and high amounts (3 vessels; 50 µM N, 3.1 µM P). The parameters necessary to calculate carbonate chemistry, chlorophyll-a concentrations, and particulate δ13C values were measured throughout the 14 day experiments. Outflow lines from the experimental vessels fed 250 ml containers seeded with juvenile blue mussels (Mytilus edulis). Mussel subsamples were harvested on days 0, 7, and 14 and their tissues were analyzed for δ13C values. We consistently observed that particulate δ13C values were positively correlated with chlorophyll-a, carbonate chemistry, and to changes in the ratio of bicarbonate to dissolved carbon dioxide (HCO3-:CO2). While the relative proportion of HCO3- to CO2 increased over the 14 days, concentrations of each declined, reflecting the drawdown of carbon associated with enhanced production. Plankton δ13C values, like chlorophyll-a concentrations, increased over the course of each experiment, with the greatest increases in the moderate and high treatments. Trends in δ13C over time were also observed in the mussel tissues. Despite ecological variability and different plankton abundances the experiments consistently demonstrated how δ13C values in primary producers and consumers reflected nutrient availability, via its impact on carbonate chemistry. We applied a series of mixed-effects models to observational data from Narragansett Bay and the model that included in situ δ13C and percent organic matter was the best predictor of [HCO3-]. In temperate, plankton-dominated estuaries, δ13C values in plankton and filter feeders reflect net productivity and are a valuable tool to understand the production conditions under which the base of the food chain was formed.